Control layer security: exploiting unobservable cooperative states of autonomous systems for secret key generation - Wei, Zhuangkun; Guo, Weisi (Institute of Electrical and Electronics Engineers (IEEE), 2024)
The rapid growth of autonomous systems (ASs) with data sharing means new cybersecurity methods have to be developed for them. Existing computational complexity-based cryptography does not have information-theoretical bounds and poses threats to superior computational attackers. This post-quantum cryptography issue indeed motivated the rapid advances in using common physical layer properties to generate symmetrical cipher keys (known as PLS). However, PLS remains sensitive to attackers (e.g., jamming) that destroy its prerequisite wireless channel reciprocity. When ASs are in cooperative tasks (e.g., rescuing searching, and formation flight), they will behave cooperatively in the control layer. Inspired by this, we propose a new security mechanism called control layer security (CLS), which exploits the correlated but unobservable states of cooperative ASs to generate symmetrical cipher keys. This idea is then realized in the linearized UAV cooperative control scenario. The theoretical correlation coefficients between Alice's and Bob's states are computed, based on which common feature selection and key quantization steps are designed. The results from simulation and real UAV experiments show i) an approximately 90% key agreement rate is achieved, and ii) even an Eve with the known observable states and systems fails to estimate the unobservable states and the secret keys relied upon, due to the multiple-to-one mapping from unobservable states (pitch, roll and yaw angles) to the observable states (3D trajectory). This demonstrates CLS as a promising candidate to secure the communications of ASs, especially in the adversarial radio environment with attackers that destroys the prerequisite for current PLS.
Keywords: Cybersecurity; cooperative control; secret key generation; wireless communication; autonomous systems